2020
DOI: 10.1016/j.ekir.2020.03.025
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Rickets in Children

Abstract: Rickets is a common bone disease worldwide that is associated with disturbances in calcium and phosphate homeostasis and can lead to short stature and joint deformities. Rickets can be diagnosed based on history and physical examination, radiological features, and biochemical tests. It can be classified into 2 major groups based on phosphate or calcium levels: phosphopenic and calcipenic. Knowledge of categorization of the type of rickets is essential for prompt diagnosis and proper management. Nutritional ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 77 publications
0
43
0
2
Order By: Relevance
“…These conditions are typical of vitamin D deficiency rickets and are less frequently observed in patients with hypophosphatemic rickets, especially XLHR. In contrast, patients with hypophosphatemic rickets can develop spontaneous dental abscesses and enamel defects [4]. Craniosynostosis, defined as the premature closure of cranial sutures, and Chiari I malformation have been reported as presenting signs in patients with XLHR [80,81].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…These conditions are typical of vitamin D deficiency rickets and are less frequently observed in patients with hypophosphatemic rickets, especially XLHR. In contrast, patients with hypophosphatemic rickets can develop spontaneous dental abscesses and enamel defects [4]. Craniosynostosis, defined as the premature closure of cranial sutures, and Chiari I malformation have been reported as presenting signs in patients with XLHR [80,81].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Tooth abscesses or facial cellulitis on apparently non-carious teeth are common and suggest poor dentin mineralization [118]. Unlike vitamin D deficiency, craniotabes, rachitic rosary, and fractures are rare [4]. Finally, recent studies have shown higher incidence of craniovertebral abnormalities, especially craniosynostosis and Chiari type 1 malformation [80,81].…”
Section: Phosphopenic Ricketsmentioning
confidence: 99%
See 2 more Smart Citations
“…In modern conditions, the risk factors for vitamin D deficiency rickets have undergone further study due to changes in socio-economic, environmental conditions of life, health state of women of childbearing age, peculiarities of physical development and infant feeding [9].…”
mentioning
confidence: 99%